Two new species of Lomandra (Asparagaceae: Lomandroideae) from north Queensland, Australia - Wang, Jian; Gray, Bruce (Phytotaxa, 2024)
Lomandra scabrifolia Jian Wang ter & B.Gray, sp. nov. and Lomandra tenuis Jian Wang ter & B.Gray, sp. nov. from north Queensland, Australia are described, illustrated and compared to the morphologically and phylogenetically closely related species. Notes are provided on their distributions including a map, habitat, phenology and affinities. Their conservation status is also assessed.